If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(2l + 7) = 72 Reorder the terms: 8(7 + 2l) = 72 (7 * 8 + 2l * 8) = 72 (56 + 16l) = 72 Solving 56 + 16l = 72 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -56 + 16l = 72 + -56 Combine like terms: 56 + -56 = 0 0 + 16l = 72 + -56 16l = 72 + -56 Combine like terms: 72 + -56 = 16 16l = 16 Divide each side by '16'. l = 1 Simplifying l = 1
| -(3+6)+2x=-(6+2)-3.3 | | 14z=18+12z | | -30-29= | | 5x+7=6z | | 12[x]1/3 | | 2y-3=5-s | | 14z=18+12m | | x^2+ab-ax-bx=0 | | 0=-5x-210 | | 2x+1=52 | | (u-8)*10=20 | | 2(-13)=4(16-u) | | 7+h=23 | | 8-c=(-12)-3c | | 4(x-2)+2=14 | | z-2=35 | | 30x=240 | | 36/12=x/3 | | -1x+4y=35 | | (q-10)*3=24 | | 27s-6=14s+7 | | 6n=10.8 | | (-153)/(9)= | | 2/3-7/9x=6x-7/9x | | 5(1+3b)=-43+9b | | X-0.5=13.5 | | A^2-14A+13=0 | | y=4E-05x+0.0746 | | 5X+73=12X-11 | | 120+(6.25)=380 | | 4x-63=2x-7 | | 2p*2-6=-11 |